Preliminary results from the MINERvA experiment - Harris D.A. (2011)
The MINERvA experiment, operating since 2009 in the NuMI neutrino beam line at Fermilab, has collected neutrino and antineutrino scattering data on a variety of nuclear targets. The detector is designed to identify events originating in plastic scintillator, lead, carbon, iron, water, and liquid helium. The goal of the experiment is to measure inclusive and exclusive cross sections for neutrino and antineutrino with much greater precision than previous experiments. We present preliminary kinematic distributions for charged current quasi-elastic scattering and other processes. © Copyright owned by the author(s) under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike Licence.